Calibration of Multi-Channel Spaceborne SAR - Challenges and Strategies - - Younis, Marwan; Laux, Christopher; Al-Kahachi, Noora; López-Dekker, Paco; Krieger, Gerhard; Moreira, Alberto (European Conference on Synthetic Aperture Radar (EUSAR), 2014)
Instrument calibration has ever been essential to synthetic aperture radar. This paper reviews the calibration functionality of current state-of-the-art spaceborne SAR and then proceeds to suggest calibration strategies for future SAR systems. These systems will incorporate multi-channel digital beamforming capabilities which offer new opportunities but also challenges for digital calibration. At the same time, the increased complexity of instrument calibration can not be extrapolated to future systems. This requires a reconsideration of the calibration strategy for spaceborne SAR. The paper is seen as a step in this direction.
DLR Import::2019-04-03